2012
DOI: 10.4049/jimmunol.1103450
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Antigens Directly Activate NK Cells via TLR2, Thus Facilitating Their Presentation to CD4 T Lymphocytes

Abstract: NK cells infiltrate human herpetic lesions, but their role has been underexplored. HSV can stimulate innate immune responses via surface TLR2, which is expressed on monocyte-derived dendritic cells (DCs) and NK cells. In this study, UV-inactivated HSV1/2 and immunodominant HSV2 glycoprotein D peptides conjugated to the TLR2 agonist dipalmitoyl-S-glyceryl cysteine stimulated CD4 T lymphocyte IFN-γ responses within PBMCs or in coculture with monocyte-derived DCs. NK cells contributed markedly to the PBMC respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
79
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 81 publications
(97 reference statements)
6
79
0
1
Order By: Relevance
“…In addition, they also have shown that NK cells alone can present Ags to CD4 T cells in the context of HSV infection after TLR activation. They suggested that this interaction could occur in herpetic lesions and also in draining lymph nodes (38). These observations support the hypothesis that cytokines, such as IL-21, involved in chronic inflammation or infections, could account for HLA-DR + NK cell differentiation (20).…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In addition, they also have shown that NK cells alone can present Ags to CD4 T cells in the context of HSV infection after TLR activation. They suggested that this interaction could occur in herpetic lesions and also in draining lymph nodes (38). These observations support the hypothesis that cytokines, such as IL-21, involved in chronic inflammation or infections, could account for HLA-DR + NK cell differentiation (20).…”
Section: Discussionsupporting
confidence: 73%
“…The molecular mechanism and physiopathological context regulating MHC-II expression and Ag presentation functions in human NK cells were never clearly investigated. In this context, Kim and colleagues (38) confirmed that activated NK cells express increased levels of MHC-II. In addition, they also have shown that NK cells alone can present Ags to CD4 T cells in the context of HSV infection after TLR activation.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…However, the TLR-induced anti-HSV2 response was abolished in IL-28R −/− mice, similar to that observed in IFNAR1 −/− (interferon alpha/beta receptor 1) mice (21). Although HSV2 antigens were recently shown to directly activate NK cells (22), the role of NK cells was not addressed using the IL-28R −/− mice. Furthermore, these mice have not been used to explore the role of IL-28R in NK cell-mediated control of tumors, nor has the relationship of host IL-28R and IFNAR1 been Significance Natural killer (NK) cells are naturally circulating innate lymphocytes that sense altered cells, including pathogen-activated and early-transformed cells.…”
mentioning
confidence: 58%